Student Satisfaction in Online Learning of Islamic Higher Education in Indonesia during the Second Wave of COVID-19 Pandemic - Munadi, Muhammad; Annur, Fauzi; Saputra, Yudi (Journal of Education and e-Learning Research, 2022)
This study aims to determine student satisfaction with online learning at UIN Raden Mas Said Surakarta Indonesia. In this study, the researchers developed new variables related to student satisfaction in online learning, such as student commitment, student independence, parental support, main source of support for online learning, student readiness, creative and innovative learning and effectiveness and behavioral intentions. The methodology used is a quantitative research method, with measurement and analysis using the smart-PLS application. The population in this study was all students of the UIN RMS Surakarta education faculty. The results of this study show that there were 412 respondents who filled out the questionnaire. After being processed using Smart-PLS there were three variables that were accepted: first, effectiveness has a significant effect on student satisfaction in online learning, second, student commitment has a significant effect on student satisfaction in online learning and third, student satisfaction has a significant effect on the behavioral intentions of students in online learning.